1999
DOI: 10.1007/bf02494629
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of oxidative carbonylation of phenylacetylene and methylacetylene. Generation and experimental discrimination of hypotheses

Abstract: Formal and informal methods for advancing hypotheses on mechanisms were used in a study of the oxidative carbonylation of phenylacetylene to methyl phenylpmpiolate catalyzed by the PdCI2--CuCI--CuCI 2 system. The hypotheses remaining after discrimination and consistent with all experimental data include the steps of formation of the Cu I alkynyi complex, transfer of the phenylethynyl group from Cu t to Pd II, insertion of carbon monoxide into a Pd--C or Pd--OMe bond of the Pd tl r complex. Comparison of the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Using a PdI 2 -KI catalyst with alkynes under mild conditions, high catalytic efficiencies have been achieved leading to a mixture of dicarbonylation products [2]. When phenylacetylene (PhAc) was used as the substrate in methanol (palladium-catalyzed phenylacetylene oxidative carbonylation, PCPOC), oscillations in pH, redox potential and gas uptake (CO and O 2 ) were discovered [3][4][5][6][7]. Further study of this reaction using power compensation calorimetry found the oscillations in pH were accompanied by oscillations in heat of reaction, Q r [8].…”
Section: Introductionmentioning
confidence: 99%
“…Using a PdI 2 -KI catalyst with alkynes under mild conditions, high catalytic efficiencies have been achieved leading to a mixture of dicarbonylation products [2]. When phenylacetylene (PhAc) was used as the substrate in methanol (palladium-catalyzed phenylacetylene oxidative carbonylation, PCPOC), oscillations in pH, redox potential and gas uptake (CO and O 2 ) were discovered [3][4][5][6][7]. Further study of this reaction using power compensation calorimetry found the oscillations in pH were accompanied by oscillations in heat of reaction, Q r [8].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, several groups proposed the application of computers for the generation of reaction mechanisms and analysis of the results. The number of generated reactions increases in a factorial measure with the increasing number of species, and this increase is even more pronounced if large molecules are involved. Therefore, most of these proposals encode expert chemical knowledge in order to avoid including unlikely reactions into the program.…”
Section: Introductionmentioning
confidence: 99%
“…MECHEM and ChemNet meet the latter requirement. They carry out mechanism elucidation by knowledge guided search within a combinatorial space to find the simplest plausible mechanisms. Thermodynamics is not incorporated into them, and they were applied mostly to catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The elementary steps tbund at the first stage served as input for MECHEM. In an experimental study ofoxidative carbonylation of phenylacetylenecatalyzed by Pd I1 and Cu I complexes 12,16,17 PhC-=CH + CO + MeOH + 2 NaOAc + 2 CuCl 2 --~ PhC-=CCOOMe + 2 AcOH + 2 NaCI + 2 CuCI, we proposed, with the assistance of a computer, 41 hypothetical mechanisms. Using these mechanisms, we were able to design a target-directed experiment based on the measurement of the kinetic isotope effect.…”
mentioning
confidence: 99%